Involvement of Ceramide Metabolism in Cerebral Ischemia - Ouro, Alberto; Correa-Paz, Clara; Maqueda, Elena; Custodia, Antía; Aramburu-Núñez, Marta; Romaus-Sanjurjo, Daniel; Posado-Fernández, Adrián; Candamo-Lourido, María; Alonso-Alonso, Maria Luz; Hervella, Pablo; Iglesias-Rey, Ramón; Castillo, José; et al. (Frontiers in Molecular Biosciences, 2022)
Ischemic stroke, caused by the interruption of blood flow to the brain and subsequent neuronal death, represents one of the main causes of disability in worldwide. Although reperfusion therapies have shown efficacy in a limited number of patients with acute ischemic stroke, neuroprotective drugs, and recovery strategies have been widely assessed, but none of them have been successful in clinical practice. Therefore, the search for new therapeutic approaches is still necessary. Sphingolipids consist of a family of lipidic molecules with both structural and cell signaling functions. Regulation of sphingolipid metabolism is crucial for cell fate and homeostasis in the body. Different works have emphasized the implication of its metabolism in different pathologies, such as diabetes, cancer, neurodegeneration, or atherosclerosis. Other studies have shown its implication in the risk of suffering a stroke and its progression. This review will highlight the implications of sphingolipid metabolism enzymes in acute ischemic stroke.